2021
DOI: 10.1002/pc.25931
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and mechanical properties of TiO2 polymer‐matrix nanocomposite and its 3D woven composite

Abstract: The present work aims to study the effect of nano-TiO 2 modified epoxy on the tension, compression, and fracture toughness properties of nano-doped polymer (NP) and nano-doped 3D woven (NW) composites. Nanoparticles are dispersed into epoxy using high-speed shear mixing and ultrasonication processes. Vacuum-assisted resin infusion molding process is utilized to prepare the woven composites. The results indicate that nanoparticle addition can

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 57 publications
(69 reference statements)
0
4
0
Order By: Relevance
“…Besides, local separations are found at the interface between the MNPs agglomeration and adhesive matrix, suggesting a relatively weak interfacial interaction and possible weakening 45 . With the increase of MNPs contents, the resin‐rich region exhibits more deflections.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, local separations are found at the interface between the MNPs agglomeration and adhesive matrix, suggesting a relatively weak interfacial interaction and possible weakening 45 . With the increase of MNPs contents, the resin‐rich region exhibits more deflections.…”
Section: Resultsmentioning
confidence: 99%
“…44 Besides, local separations are found at the interface between the MNPs agglomeration and adhesive matrix, suggesting a relatively weak interfacial interaction and possible weakening. 45 With the increase of MNPs contents, the resin-rich region exhibits more deflections. Hence, the interfacial interaction between adhesive and MNPs should be carefully treated and enhanced for magnetocuring process in future practice.…”
Section: Fracture Morphologymentioning
confidence: 98%
“…Guo et al 32 found that TiO 2 nanoparticles were successfully incorporated to form nanocomposites using an injection molding technique. Gong et al 33 noted enhancement in compressive strength and fracture toughness of nano‐TiO 2 incorporated woven fabric‐reinforced composites. Mahesha et al 34 found that there is an excellent improvement in mechanical property of jute‐hemp fiber with the incorporation of titanium oxide particles.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that incorporating nanofillers into EP is the most efficient way to enhance the toughness of EP. For instance, graphene oxide (GO), [15] nanoclay, [16] graphene nanoplatelets (GnPs), [17] carbon nanotubes (CNTs), [13,[18][19][20] MoS 2, [7] SiO 2, [21] TiO 2, [9,22,23] and Si 3 N 4 [24] have been used to improve the toughness of EP polymers. However, owing to the easy agglomeration and the deficient active groups of those nanoparticles, the dispersion of nanoparticles in matrix is poor and the filler/matrix interface is weak, resulting in inefficient load transfer.…”
mentioning
confidence: 99%